Programas de intervenção para a promoção de habilidades sociais usadas em contextos profissionais: uma revisão de literatura - Castro, Valentina Joana Rocha (Universidade Federal de São Carlos, 2025)
Social skills are essential for the quality of interpersonal interactions and professional performance. Although there are studies about the effects of social skills intervention programs in clinical and educational contexts, an analysis of the results of different workplace intervention programs, in Brazil, has not been conducted.. Therefore, the objective of this study was to identify and analyze studies describing social skills training programs conducfed in Brasil, considering their effects on social behavior and the quality of workplace relationships. Searches were conducted in the SciELO, CAPES Periódicos, and the Biblioteca Digital de Teses e Dissertações databases, including empirical studies with qualitative or quasi-experimental designs that were published between 2017 and 2023. Data were extracted and organized into tables covering study design, participants, objectives, intervention strategies, evaluation procedures, and outcomes. A total of 11 studies were included, most of which used qualitative designs and had predominantly female participants aged between 30 and 50 years. The strategies used in the intervention programs included dramatizations, group dynamics, practical tasks, and online courses. Reported outcomes included improvements in empathy, assertiveness, leadership, and communication, with some studies presenting large effect sizes (e.g., d = 1.21 for leadership). In conclusion, the programs had theoretical consistency and positive effects on workers’ socioemotional development. However, controlled randomized studies are needed, with larger samples that are more representative of the Brazilian population of workers, using instruments that have satisfactory evidence of reliability and validity, and follow-up studies, to establish more robust evidence concerning the efficacy and the contributions of social skills training programs for paid workers.
Intervention programs for promoting social skills in the workplace: a literature review
Keywords: Habilidades sociais; Relações interpessoais; Trabalho; Treinamento; Social skills; Interpersonal relationships; Work; Training; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO TRABALHO E ORGANIZACIONAL::TREINAMENTO E AVALIACAO; 3. Saúde e Bem-Estar; 8. Trabalho Decente e Crescimento Econômico